Comprehensive characterization of RSPO fusions in colorectal traditional serrated adenomas. Issue 4 (11th July 2017) - Sekine, Shigeki; Ogawa, Reiko; Hashimoto, Taiki; Motohiro, Kojima; Yoshida, Hiroshi; Taniguchi, Hirokazu; Saito, Yutaka; Yasuhiro, Ohno; Ochiai, Atsushi; Hiraoka, Nobuyoshi
Abstract : Aims: Traditional serrated adenoma (TSA) is a rare but distinct type of colorectal polyp. Our previous study showed that PTPRK – RSPO3 fusions are frequent and characteristic genetic alterations in TSAs. This study aimed to characterize comprehensively the prevalence and variability of RSPO fusions in colorectal TSAs. Methods and results: We examined RSPO expression and explored novel RSPO fusions in 129 TSAs, including 66 lesions analysed previously for WNT pathway gene mutations. Quantitative polymerase chain reaction (qPCR) analyses identified three and 43 TSAs overexpressing RSPO2 and RSPO3, respectively, whereas the expression of RSPO1 and RSPO4 was marginal or undetectable in all cases. RSPO overexpression was always mutually exclusive with other WNT pathway gene mutations. Known PTPRK–RSPO3 fusions were detected in 37 TSAs, all but one of which overexpressed RSPO3 . In addition, rapid amplification of cDNA ends revealed three novel RSPO fusion transcripts, an NRIP1–RSPO2 fusion and two PTPRK–RSPO3 fusion isoforms, in six TSAs. Overall, 43 TSAs had RSPO fusions (33%), whereas four TSAs (3%) overexpressed RSPO in the absence of RSPO fusions. TSAs with RSPO fusions showed several clinicopathological features, including distal localization ( P = 0.0063), larger size ( P = 0.0055), prominent ectopic crypt foci ( P = 8.4 × 10 −4 ), association of a high‐grade component ( P = 1.1 × 10 −4 ), and the presence of KRAS mutations ( P = 4.5 × 10 −5 ). Conclusions: The present study identified RSPO fusion transcripts, including three novel transcripts, in one‐third of colorectal TSAs and showed that PTPRK–RSPO3 fusions were the predominant cause of RSPO overexpression in colorectal TSA.